Managing childhood atopic dermatitis: exploring caregivers’ barriers and facilitators to treatment adherence at a public hospital in the Western Cape, South Africa - Field, Courtney Anne (Stellenbosch : Stellenbosch University, 2022)
Thesis (MA)--Stellenbosch University, 2022